Competency Versus Proficiency in Pediatric Orthopaedic Training - Alman, Benjamin A. (Journal of the Pediatric Orthopaedic Society of North America, 2022)
As pediatric orthopaedics has grown in size and scope, standardization of training is being considered as a way to ensure unform standards. Competency is the knowledge, skill, and judgment to successfully complete a task, but one that the trainee has not yet demonstrated that they can achieve on their own. Proficiency occurs when a task can be accomplished independently. Defining the standards for competency and proficiency are needed to develop such standards. In the North American context, residency is where competency is achieved and fellowship is a time in which pediatric orthopaedists achieve proficiency, although, for some highly specialized tasks, competency is also the goal of fellowship training. Attaining and assessing competency and proficiency can be accomplished using a structured curriculum and assessments. These do not necessarily require simulations, as observations in the clinical setting are useful for assessing proficiency. Defining the competencies and proficiencies required for pediatric orthopaedics and developing standard methods of assessment will ensure that pediatric orthopaedics fellowship trainees have acquired the base knowledge, judgment, and technical skills to be a safe and effective clinician.